2022
DOI: 10.2196/38181
|View full text |Cite
|
Sign up to set email alerts
|

Early Detection of Neurodevelopmental Disorders of Toddlers and Postnatal Depression by Mobile Health App: Observational Cross-sectional Study

Abstract: Background Delays in the diagnosis of neurodevelopmental disorders (NDDs) in toddlers and postnatal depression (PND) in mothers are major public health issues. In both cases, early intervention is crucial. Objective We aimed to assess if a mobile app named Malo can reduce delay in the recognition of NDD and PND. Methods We performed an observational, cross-sectional, data-based study in a population of young… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(18 citation statements)
references
References 27 publications
0
18
0
Order By: Relevance
“…Practices based on the family-centered model ensure family commitment and are related to positive therapeutic outcomes [ 41 , 42 , 43 , 44 , 48 , 53 , 59 , 61 , 63 , 64 , 65 ]. As shown in the previous section, variables such as competence, self-efficacy, satisfaction, and empowerment are of great importance since, to some extent, the intervention will depend on them.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Practices based on the family-centered model ensure family commitment and are related to positive therapeutic outcomes [ 41 , 42 , 43 , 44 , 48 , 53 , 59 , 61 , 63 , 64 , 65 ]. As shown in the previous section, variables such as competence, self-efficacy, satisfaction, and empowerment are of great importance since, to some extent, the intervention will depend on them.…”
Section: Resultsmentioning
confidence: 99%
“…Subsequent research continues this line of prevention and intervention in determining aspects of the health of infants aged 0 to 6 years, showing rates of effectiveness and acceptability, in which the figure of the family and its context are highlighted in the process [ 42 , 45 , 51 , 53 , 54 , 57 ].…”
Section: Resultsmentioning
confidence: 99%
“…The forest plot as shown in Figure 2 below provides a clear interpretation of the findings of this study [14][15][16][17][18][19][20][21][22][23][24][25][26]. The columns indicate the included studies, the intervention group, the control group, the weight, and the outcome effect in the numerical and graphical format [27].…”
Section: Forest Plotmentioning
confidence: 97%
“…For instance, the effectiveness of the ESDM model for treating and managing developmental delays arising from autism spectrum disorder was noted [ 15 , 16 ]. A study identified an algorithm-based mobile application named Malo to effectively diagnose and recognize NDD and post-natal depression (PND) [ 18 ]. Also, a model-based study proposed using the Bayesian network (BN) model to predict early motor development problems for delayed children [ 19 ].…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation